2017
DOI: 10.2337/db16-1569
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced MicroRNA-708 Impairs β-Cell Function and Growth

Abstract: The pancreatic β-cell transcriptome is highly sensitive to external signals such as glucose oscillations and stress cues. MicroRNAs (miRNAs) have emerged as key factors in gene expression regulation. Here, we aimed to identify miRNAs that are modulated by glucose in mouse pancreatic islets. We identified miR-708 as the most upregulated miRNA in islets cultured at low glucose concentrations, a setting that triggers a strong stress response. miR-708 was also potently upregulated by triggering endoplasmic reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…Of note, overexpression of Neuronatin restored the Glucose-Stimulated Insulin Secretion (GSIS) in murine and human islets cultured at low glucose levels. These results demonstrated that miR-708 could be used as potential target to restore β cell function under stress conditions [52,53].…”
Section: Mirnas β Cell Function and Oxidative Stressmentioning
confidence: 73%
“…Of note, overexpression of Neuronatin restored the Glucose-Stimulated Insulin Secretion (GSIS) in murine and human islets cultured at low glucose levels. These results demonstrated that miR-708 could be used as potential target to restore β cell function under stress conditions [52,53].…”
Section: Mirnas β Cell Function and Oxidative Stressmentioning
confidence: 73%
“…By targets Argonaute2, miR-184 plays adaptive role of the miRNA pathway based on metabolic state ( 27 ). Stress-induced overexpression of miR-708 suppressed β-cell proliferation and induced β-cell apoptosis, which provide a novel mechanism of glucose regulation of β-cell function and growth ( 28 ). Comparing to tissue biomarkers, circulating miRNAs are preferred due to easier sampling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…Also, upregulation of NFE2L2 by increasing miR-200a protected against diabetic nephropathy in mice treated with an analogue of curcumin [42]. Similarly, miR-708 was potently upregulated by triggering ER stress in pancreatic islets of ob/ob mice, whose overexpression suppressed b-cell proliferation and induced b-cell apoptosis [43]. Additionally, it was demonstrated that a modest increase in maternal dietary fat in mice programmed triglyceride storage in the liver of their offspring at the adult stage that was controlled by the eIF2a kinase Gcn2 (Eif2ak4), which stimulated epigenetic modification (trimethylation of lysine 4 of histone 3) at the Pparg2 gene in the neonatal liver [44].…”
Section: Epigenetics Of Er Stress Dyslipidemia and Insulin Resistancementioning
confidence: 94%